Estudo da adulteração com fármacos de suplementos alimentares para emagrecimento e avaliação in silico da interação fármaco-alimento entre sibutramina e grapefruit - Moreira, Ana Paula Lançanova (2016)
Dietary supplements are considered safe products for consumption because many of them are from natural source. The consumption of these products has increased as an alternative in the prevention and treatment of several diseases. However, dietary supplements are not under strict requirements regarding proof of safety and efficacy as it is required for synthetic drugs, and numerous reports of adverse events have been observed with increasing consumption of these products. The reactions can be the result of adulteration with synthetic drugs or drug interactions between components of these formulations and other prescription drugs. The risk of food-drug interactions becomes even greater with the presence of drugs not declared in adulterated dietary supplements. Considering this, this thesis proposed the development of an analytical method by LC-MS / MS for determination of 33 adulterants (anorectics, stimulants, diuretics, laxatives, anxiolytics and antidepressants) in slimming dietary supplements. In addition, it was proposed the development of a physiologically based on pharmacokinetic (PBPK) model by Simcyp Simulator to estimate the pharmacokinetic exposition of sibutramine and its two active metabolites, evaluating the risk of drugfood interactions when administrated simultaneously with grapefruit in the treatment of obesity. The method developed by LC-MS / MS employed an electrospray ionization source (ESI) with application of 350 °C of temperature for the drying gas, gas flow rate of 10 L min-1, nebulizer pressure of 30 psi and 2000 V for capillary voltage. The separation of the compounds was in a Zorbax column (2.1 x 50 mm, 1.8μm) in a gradient with acetonitrile and formic acid 0.05% (v/v) allowing the separation of 33 adulterants in 15 minutes. Extraction of samples was performed with methanol in ultrasonic bath during 15 minutes and filtration in hydrophobic membrane 0.2 μm. The method was applied in 114 samples of dietary supplements. Caffeine was the stimulant most frequently declared and detected in the formulations followed by synephrine (Citrus aurantium). However, caffeine and synephrine were also found as adulterants in two formulations that did not contain these substances or other compounds containing caffeine such as green tea or guarana, or synephrine as C.aurantium declared on the label. The PBPK model, developed for sibutramine and its active metabolites, employed an ADAM absorption process, sibutramine in vitro metabolism data and clinical trial data obtained from literature that allowed approaching the model to the in vivo drug disposition, improving the prediction for drug-drug interaction studies. The drug-drug interaction between sibutramine, a CYP3A4 substrate, with grapefruit, a competitive and irreversible inhibitor of CYP3A4 enzyme, both with slimming action, was evaluated by simulating the simultaneous use in the treatment of obesity. Grapefruit increased in 25% the exposure to sibutramine, what can increase the therapeutic effect but above all, can potentiate the adverse effects of this drug, which leaded the sibutramine to be withdrawal from the market in many countries. Based on the conducted study we found that dietary supplements are not free of health risks to users. Assessing the safety of these products has become an important issue for the regulatory agencies and health professionals in order to ensure treatment of quality, without increase damage to the users.